EFL LEARNERS’ TENDENCY IN USING CONJUNCTIONS IN WRITINGS: EVIDENCE FROM ENGLISH DIPLOMA-III STUDENTS - Zewitra Zewitra; Krisna Yudha Bakhti; Muhamad Salam Ramadhan (PROJECT (Professional Journal of English Education), 2023)
The conjunction is known as one of the most challenging topics to acquire by EFL learners. Its close correlation with the ability of writing makes this topic imperative to master by English learners. The study intends to identify (1) the types of conjunction used by EFL learners in writing English texts, and (2) the combinations formed by using conjunction in writing English texts. Data was collected from the background part of final project reports of English Diploma-III students of Politeknik Negeri Bandung, Indonesia. It resulted in 213 uses of conjunctions to be further analyzed. This study employed the qualitative descriptive method to identify the type of conjunction used and the model of combinations formed. The results show that EFL learners have been able to use coordinate conjunction, subordinate conjunction, and correlative conjunction in writing English texts. The most conjunction used is the coordinate conjunction. Also, they have been able to form combinations of word-word, word-phrase, phrase-phrase, and clause-clause by using conjunctions in their English writings. These results may bring both theoretical and practical implications. First, theoretically, the findings can enrich the knowledge of English Grammar and Writing in general. Second, practically, the results may be beneficial for curriculum designers and lecturers as one of the evaluation resources to arrange more suitable materials for EFL learners, especially at the level of Diploma-III.      Keywords:  Conjunction; Final Project; Background; EFL Learners